Symmetrization, vortex Rossby waves, and hurricane motion in an asymmetric balance model - Kallenbach, Randall J., author; Montgomery, Michael T., author (Colorado State University. Libraries, 1995)
The complexity of primitive equation (PE) models commonly used for forecasting hurricane track and structure changes can often make interpretation of their output difficult and speculative. A simplified balance formulation of these phenomena is desirable to further understand the physics of rapidly rotating storms. This work presents a shallow-water numerical model suitable for simulating hurricane track and evolution based on asymmetric balance (AB) theory. The model is a shallow-water formulation of AB, that incorporates rapid rotation and permits order-one divergence. The solution technique employed is a pseudo-spectral azimuthal modes model utilizing grid points radially and Fourier modes azimuthally. In this work we also consider the process of vortex axisymmetrization as a model for outward-propagating spiral bands in hurricanes. The basic physics is illustrated most sim ply for stable potential vorticity monopoles on an £-plane. Unlike the dynamics of sheared disturbances in rectilinear shear flow, symmetrizing disturbances on vortex monopoles are accompanied by outward-propagating Rossby waves whose restoring mechanism is associated with the vortex potential vorticity gradient. Expressions for phase and group velocities are derives and verified that confirm early speculations on the existence of vortex Rossby waves in hurricanes. The theory is applied to a hurricane-like vortex and the results are consistent with radar observations. The wave mechanics developed here shows promise in elucidating basic mechanisms of hurricane evolution and structure changes, such as the formation of secondary eyewalls.
June 1995.
Keywords: Hurricanes -- Tracks; Vortex-motion